2014
DOI: 10.12691/ijdsr-2-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Granuloma- a Case Report and Review

Abstract: Exophytic gingival lesions represent some of the more frequently encountered lesions in the oral cavity.Some of these lesions are reactive in nature. Pyogenic granuloma is a relatively common benign mucocutaneous lesion occurring intra orally or extra orally. The exact etiopathogenesis remains unknown, although contributory factors include trauma, inflammation and infectious agents. Intraoral lesions are sometimes associated with pregnancy. Typically, pyogenic granuloma presents as an exuberant, red painless m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Some authors claimed that the condition was initially reported by Hullihen in 1844, and the term pyogenic granuloma was established by Hertzel in 1904. Others claimed that Poncet and Dor originally reported the condition in 1897 as botryomycosis hominis, as they had suspected a fungal cause, while Crocker later introduced the term pyogenic granuloma in 1903 [ 2 , 3 , 5 , 11 ]. Hence, disagreement in the literature concerning PG's first report and nomenclature exists.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors claimed that the condition was initially reported by Hullihen in 1844, and the term pyogenic granuloma was established by Hertzel in 1904. Others claimed that Poncet and Dor originally reported the condition in 1897 as botryomycosis hominis, as they had suspected a fungal cause, while Crocker later introduced the term pyogenic granuloma in 1903 [ 2 , 3 , 5 , 11 ]. Hence, disagreement in the literature concerning PG's first report and nomenclature exists.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PG usually manifests as a solitary, soft, exophytic, painless, pinkish-to-red mass with a pedunculated or sessile base that can be easily injured, causing bleeding [ 3 , 14 ]. However, in our clinical case, it was pinkish to red in color with a rubbery base.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations